2018
DOI: 10.9734/acri/2018/41176
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Climate Change on Swamp Rice Cultivation by Farmers in Ebonyi State, Southeastern Nigeria

Abstract: The perception of changes in climate in any environment by farmers significantly influences their ability to adjust and cope with challenges that might emerge from such changes. Climate change can have direct impact on swamp rice cultivation because swamp rice cultivation in Ebonyi State is rain-fed. This impact is particularly significant as swamp rice farming constitutes a major source of income and employment in the area. The study thus examined the perceived impact of climate change on swamp rice cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The study showed that the majority (72.22%) of the farmers were males. This is in line with some studies like Diagi and Nwagbara [34], which asserted that agriculture is dominated by males (73.7%). This, however, goes against another work by Igboeji et al [35], who identified that females are the majority (58.3%) of small-scale rice farmers in Ebonyi.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The study showed that the majority (72.22%) of the farmers were males. This is in line with some studies like Diagi and Nwagbara [34], which asserted that agriculture is dominated by males (73.7%). This, however, goes against another work by Igboeji et al [35], who identified that females are the majority (58.3%) of small-scale rice farmers in Ebonyi.…”
Section: Resultssupporting
confidence: 92%
“…This is not far from the finding of Ifeanyi-Obi et al [33] in which the average age of cocoyam farmers in Southeast Nigeria was found to be 51 years. It is also not far from the findings of Diagi and Nwagbara [34], which asserted that the majority of the swamp rice farmers in Ebonyi State fall around the age of 40. The implication of this is that able-bodied youths are not many in the study area, and the aged available farmers were known for the traditional methods of their forefathers.…”
Section: Resultsmentioning
confidence: 56%
“…Consequently, the lengths and intensities of rainfall have increased, producing large runoffs and flooding in many parts of Nigeria [26]. As a result, farmers in Ebonyi state have noticed the impact of climate change in rice cultivation [27]. The farmers observed an increase in swamp size implying more land area available for swamp rice cultivation.…”
Section: Farmers Perception Of Climate Change In Southeast and Their mentioning
confidence: 99%
“…All over the world, adverse effects of climate change have become a national concern particularly in the agricul-tural sector [1]. This concern is due to the fact that climate change is creating unfavorable challenges in advancement of agriculture, food security and the general wellbeing of man [2] .…”
Section: Introductionmentioning
confidence: 99%
“…[3] asserted that agriculture will significantly be *Corresponding Author: Diagi B.E, Department of Environmental Management, Federal University of Technology, Owerri, Nigeria; E-mail: edeoli@yahoo.com affected by damage caused by changes in climate. Rice farming, particularly those dependent on rainfed, need certain acceptable climatic parameters to produce optimally and therefore are in danger due to climate change [4] especially if it comes with unfavorable conditions [1] . In Nigeria, production of crops and its yield is largely determined by variation in climatic factors mainly rainfall and temperature [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%